KAJIAN DOSIS PUPUK N DAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum. L) : Kata kunci: Pupuk N, Pupuk Kandang Kambing, Pertumbuhan, Hasil, Bawang Merah - Dwi nofiyanto; Priyono Priyono; Siswadi Siswadi (Innofarm:Jurnal Inovasi Pertanian, 2023)
This study entitled "Study of Dosage of N Fertilizer and Goat Manure on the Growth and Yield of Shallots (Allium Ascalonicum. L)". The aim was to study the effect of N fertilizer and goat manure on the growth and yield of shallot plants. Implementation on 18 November 2022 to 20 January 2023 in Senayu Hamlet, Tunggur Village, Kec. Slogohimo, Kab. Wonogiri, Central Java. The method used is RAKL Factorial with 2 factors. Factor 1 was goat manure (K) with 3 levels, including: K0 = Control, K1 = 100 g/plant, and K2 = 200 g/plant. Factor 2 is the dose of N fertilizer with 4 levels, as follows: D0 = No treatment, D1 = 0.5 gr/plant, D2 = 1 gr/plant, and D3 = 1.5 gr/plant. So that from the design there are 12 combinations and repeated 3 times. Parameter data were analyzed using ANOVA and then continued using the 5% level DMRT test. The conclusion shows that the dose of N fertilizer affects the observation of the number of leaves, the application of goat manure affects the observation of plant height, tuber diameter, and tuber fresh weight per plant. The interaction of N fertilizer doses and goat manure does not affect all parameters.